Warren Buffett / Robert Heller ; penerjemah Irzam Hardiansyah ; editor Theresia Vini, Ratri Medya,Yati Sumiharti - Heller, Robert; Hardiansyah, Irzam; Vini s, Theresia; Medya, Ratri; Sumiharti, Yati (Esensi, 2008)
111 hlm ilus 21 cm